CAUSES OF GLACIATION IN SIBERIA ON TRANSITION FROM KASANTZEVO CLIMATE OPTIMUM TO ZYRJANIAN ICE AGE (FROM CLIMATE RECORDS IN BAIKAL BOTTOM SEDIMENTS) - Prokopenko A.A.; Karabanov E.B.; Kuz'min M.I.; Williams D.F. (My University, 2001)
We discuss stratigraphic and correlational age modeling of the Baikal sediment record and summarize studies of paleoclimate records in cores from various regions of Lake Baikal. The available paleoclimate reconstructions attest to an abrupt strong Early Wurm glaciation in the Baikal region at the oxygen isotope substage 5d, (117-105 ka BP). This confirms the existence of an "additional" glaciation predicted for Siberia from paleoclimate modeling and suggests a regional mechanism responsible for the intensity of this glaciation, which was better pronounced in Siberia than elsewhere in the Northern Hemisphere. The available data on the Early Zyrjanian glaciation in Siberia, provide an insight into the space-time dynamics of the origin of the Early Wurm glaciation and can account for the discrepancy between a considerable (about 40%) increase in global ice volume at the substage 5d and the lack of physical evidence for glaciation from other regions of the Northern Hemisphere. Catastrophic events of the 5e/5d transition revealed in the Baikal sediment record and in other Siberian data indicate a significant role of Siberia in climate-forming processes in the Northern Hemisphere.